Kinetic and Thermal Studies of Adsorption of Allura Red Dye by Surface Functionalized Magnetite Nanoparticles - Singh, Jaiveer; Jangra, Arti; Rani, Keerti; Kumar, Parvin; Kumar, Suresh; Kumar, Ramesh (Asian Journal of Chemistry, 2021)
In the present study, chitosan functionalized magnetite nanoparticles (CS@MNPs) were synthesized by a simple and economical coprecipitation technique for efficient magnetic removal of allura red dye (ARD) by adsorption technique from the aqueous solution. Size and surface properties of the bare and surface functionalized MNPs were determined with the help of XRD and TEM technique. Surface functionalization of the bare MNPs was confirmed with the help of FT-IR spectroscopy and TGA techniques. Magnetic properties of the synthesized bare and functionalized MNPs were determined by VSM technique. The effect of various parameters including adsorbent dosages, contact time, temperature on adsorption capacity of the CS@MNPs for allura red dye were investigated with the help of UV-vis spectrophotometer. The pseudo second order kinetics and Langmuir adsorption isotherm model were found to fitted well with the adsorption process of dye onto the chitosan functionalized magnetite nanoparticles (CS@MNPs).